“Influencer marketing: the impact of online influencers on Generation Y’s purchase intention in China” - Jin, Ming (2023)
With the accelerated expansion of e-commerce in China, "influence marketing," which demonstrates the dazzling growth curve, has become a preferred choice among customers. With the growth of this new revolution, the consumption market and social media are no longer completely independent. With the development of this new revolution, the consumption market and social media are no longer completely independent. The audiences will indeed be granted the option to choose social media; additionally, social media platforms should dynamically fulfil the consumer's expectations. E-commerce platforms and digital marketing strategies are becoming crucially influential. Whereas the online business is continuously growing, more vertical sub-sectors have adopted in influence marketing.